Myeloid-derived suppressor cells are associated with impaired Th1 and Th17 responses and severe pulmonary paracoccidioidomycosis which is reversed by anti-Gr1 therapy - Preite, Nycolas Willian; Kaminski, Valéria de Lima; Borges, Bruno Montanari; Calich, Vera Lúcia Garcia; Loures, Flávio Vieira (Frontiers in Immunology, 2023)
Previous studies on paracoccidioidomycosis (PCM), the most prevalent systemic mycosis in Latin America, revealed that host immunity is tightly regulated by several suppressive mechanisms mediated by tolerogenic plasmacytoid dendritic cells, the enzyme 2,3 indoleamine dioxygenase (IDO-1), and regulatory T-cells (Tregs). IDO-1 orchestrates local and systemic immunosuppressive effects through the recruitment and activation of myeloid-derived suppressor cells (MDSCs), a heterogeneous population of myeloid cells possessing a potent ability to suppress T-cell responses. However, the involvement of MDSCs in PCM remains uninvestigated. The presence, phenotype, and immunosuppressive activity of MDSCs were evaluated at 96 h, 2 weeks, and 8 weeks of pulmonary infection in C57BL/6 mice. Disease severity and immune responses were assessed in MDSC-depleted and nondepleted mice using an anti-Gr1 antibody. Both monocytic-like MDSCs (M-MDSCs) and polymorphonuclear-like MDSCs (PMN-MDSCs) massively infiltrated the lungs during Paracoccidioides brasiliensis infection. Partial reduction of MDSC frequency led to a robust Th1/Th17 lymphocyte response, resulting in regressive disease with a reduced fungal burden on target organs, diminishing lung pathology, and reducing mortality ratio compared with control IgG2b-treated mice. The suppressive activity of MDSCs on CD4 and CD8 T-lymphocytes and Th1/Th17 cells was also demonstrated in vitro using coculture experiments. Conversely, adoptive transfer of MDSCs to recipient P. brasiliensis-infected mice resulted in a more severe disease. Taken together, our data showed that the increased influx of MDSCs into the lungs was linked to more severe disease and impaired Th1 and Th17 protective responses. However, protective immunity was rescued by anti-Gr1 treatment, resulting in a less severe disease and controlled tissue pathology. In conclusion, MDSCs have emerged as potential target cells for the adjuvant therapy of PCM.